Effect of pounding on multistorey adjacent elastic RC buildings without seismic gaps under earthquake excitation - Khante, S.N.; Kale, A.D. (Journal of Structural Engineering, 2024)
It is observed during past earthquakes that adjacent buildings get damaged due to pounding and sometimes it leads to collapse of the building. It is also observed that at the thermal expansion joint provided in building, at common wall between adjacent buildings pounding takes place due to inadequate gap, buildings hit each other and may lead to damage and sometimes complete collapse of the building. Pounding may happen to similar or dissimilar buildings of same or different heights. This paper investigates the pounding effect on two adjacent mutistorey RC buildings during earthquake using building models with different seismic gaps. The time history analysis of two adjacent symmetric and unsymmetrical buildings with five different models with load transfer from node to node and from node to column was carried out using finite element based software and effect of pounding is observed for those building for maximum axial force, shear force and bending moment and joint displacement.